Prevalence of developmental coordination disorder in children aged 7 to 10 years. http://dx.doi.org/10.5007/1980-0037.2013v15n2p233 - Viviane Aparecida Pereira dos Santos; José Luiz Lopes Vieira (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
Children’s movements are initially characterized by inconsistent and imprecise actions. However, with practice and experience, the motor patterns become more refined and they present better coordination and control. However, it is not rare to observe children that manifest certain movement difficulties that might interfere in the children’s emotional, affectionate, school and social relationships. We investigated the prevalence of Developmental Coordination Disorder (DCD) in schoolchildren aged 7 to 10 years and which motor tasks the children with probable DCD and risk of DCD present larger motor difficulty. The evaluation included 581 children registered regularly from the 2nd to the 5th grade of Elementary School of public schools of Maringá-PR was conducted through the battery II and III of the Movement Assessment Battery for Children (MABC) test. The results indicated that 78,1% of the children present Typical Development (DT), 10,5% presented risk of Developmental Coordination Disorder (Risk of DCD) and 11,4% were diagnosed with potential Developmental Coordination Disorder (Potential DCD). Therefore, the results showed high prevalence of population for Risk of DCD and Potential DCD, predicting unfavorable levels in the acquisition and improvement of fundamental skills, which may harm the continuity of the process of the children’s motor development. Manual skills were the major motor difficulty found in children with DT while ball skills were the major motor difficulty in children with probable DCD and risk of DCD.